An Introduction to the Theoretical Aspects of Coloured Petri Nets - Jensen, Kurt (DAIMI Report Series, 1994)
This paper presents the basic theoretical aspects of Coloured Petri Nets (CP-nets or CPN). CP-nets have been developed, from being a promising theoretical model, to being a full-fledged language for the design, specification, simulation, validation and implementation of large software systems (and other systems in which human beings and/or computers communicate by means of some more or less formal rules). The paper contains the formal definition of CP-nets and their basic concepts (e.g., the different dynamic properties such as liveness and fairness). The paper also contains a short introduction to the analysis methods, in particular occurrence graphs and place invariants. The development of CP-nets has been driven by the desire to develop a modelling language - at the same time theoretically well-founded and versatile enough to be used in practice for systems of the size and complexity that we find in typical industrial projects. To achieve this, we have combined the strength of Petri nets with the strength of programming languages. Petri nets provide the primitives for the description of the synchronisation of concurrent processes, while programming languages provide the primitives for the definition of data types and the manipulation of their data values.